Analysis of Self Control With Student's Learning Achievement at Smk Kemala Bhayangkari Delog Jakarta - Prasetyo, Rafly (Green Publisher Indonesia, 2022)
The destination study this to analyze control self with performance study students at SMK Kemala Bhayangkari Delog Jakarta, of course, can make as a reference in making school policy _, especially at SMK Kemala Bhayangkari Delog. Many are found in school, especially high school, students often have common problems _ that occur in school fighting, enmity, cheating, each other ridicule, and declining grades _ as well as academic stress, change demands study from the past also caused appearance stress symptoms. The method of research used _ in a study is method descriptive qualitative. Obtained results that connection control self student with performance study each other get in touch. The facts found at SMK Kemala Bhayangkari Delog class XI, some students can't control themselves so which results in low-performance study students. Desire every indicated individual _ through the achievements he has made. Success for a student if capable show performance through results good study